DAMPAK REFORMA AGRARIA DARI BAWAH TERHADAP KESEJAHTERAAN MASYARAKAT DI DESA GARONGAN DAERAH ISTIMEWA YOGYAKARTA - Sokoastri, Valentina; Soetarto, Endriatmo (Sodality: Jurnal Sosiologi Pedesaan, 2012)
Agrarian reform by leverage or commonly known as landreform by leverage is a peasant movements which is organized by peasant initiative to defend their land. This movement could be associated with social welfare and negative excess like criminalization that frequently take place in Garongan village. There, most people involved in conflict because of their persistence to keep their land. There is a strong relationship between agrarian reform by leverage and peasant welfare. Land which is frequently referred as crucial donation of life has a vital value for human survival. The function of land is not only considered as human nee ds but  al so as i dent it y t hat  al ways  t ri ggers  any c onfl i ct  nowadays . So, it ’s not  st range if  thi s condi ti on causes any negative impacts of criminalization including psychological, physical or both psychological and physical effects for those who involved. At the end of this description, farmers who have been sovereign from agriculture will be interferred by iron sand mining company which is supported by feudal forces and private corporations. This research examine more deeply about the relationship between agrarian reform by leverage and social welfare, the impact of agrarian reform by leverage to the criminalization and the differences of level of social welfare before and after agrarian reform in Garongan village. Keywords: agrarian reform by leverage, criminalization, social welfare.